Study of the association between the interleukin-1 β c.3954C>T polymorphism and periodontitis in a population sample from Bahia, Brazil - Samir A Mendonça; Fernanda G Teixeira; Kamilla M Oliveira; Djanilson B Santos; Lucas M Marques; Maise M Amorim; Raquel De S. Gestinari (Wolters Kluwer Medknow Publications, 2015)
Background: Periodontitis is an inflammatory disease characterized by the loss of connective tissue and alveolar bone. Different factors are associated with the onset and prognosis of this disease, both environmental and genetic. The latter particularly relate to molecules secreted as a function of the host immune response, such as pro-inflammatory cytokines. Studies indicate that the polymorphism c. 3954C > T in the interleukin-1 β encoding gene (IL1B) can be considered as an aggravating factor in the periodontitis condition. Aims: This study aimed to evaluate whether there is an association between the IL1B c. 3954C > T gene polymorphism and the prevalence of periodontitis in the population from Vitσria da Conquista-Bahia, Brazil. Materials and Methods: A total of 347 subjects (134 cases and 213 controls) who provided epithelial tissue of the oral cavity and saliva samples for DNA extraction and quantification of IL1B, respectively, were selected. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism followed by electrophoresis in agarose gel. The evaluation of the cytokine concentration was performed by enzyme-linked immunosorbent assay. Statistical Analysis: Statistical calculations involved in this work include Chi-square test, Fisher Exact test, Mann-Whitney and Kruskal-Wallis tests. Results: Our findings revealed that: (i) No statistically significant relationship between periodontitis and the polymorphism studied was observed; (ii) no significant difference between the concentrations of IL1B in saliva between the case and control subjects and between the genotypes of these individuals and the concentrations of this cytokine. Conclusions: We conclude that, in the sample evaluated, the IL1B c. 3954C > T polymorphism did not present as an etiological factor for periodontitis.